Recent trends in international migration in Poland: The 2013 SOPEMI report - Marta Anacka; Igor Jakubiak; Paweł Kaczmarczyk; Karolina Łukaszczyk; Renata Stefańska (University of Warsaw, Centre of Migration Research (CMR), 2015)
This Working Paper presents a SOPEMI report for Poland for 2013. It focuses on the most important recent developments in migration policy and offers an overview of migration trends to and from Poland. Specifically, it includes a brief analysis of recent economic developments shaping migration from and into Poland, changes in migration policy of Poland, recent trends in the transborder mobility, emigration from Poland and immigration to Poland. The statistical annex includes all data concerning the recent trends in migration from and into Poland.
Keywords: 330; international migration; emigration; immigration; migration policy; Poland; SOPEMI report